The Desperate Hours - William Wyler; Kennedy, Arthur, 1914-1990.; Dewey Martin; Fredric March; Gig Young; Martha Scott; Mary Murphy; Humphrey Bogart (USA Paramount Pictures, 1955)
Dan Hilliard is a comfortable upper-middle-class executive with a wife and two children and a pleasant suburban home. His world seems quite in order, quite predictable. But then convicted murderer Glenn Griffin escapes from prison with his younger brother Hal and a ruthless thug named Kobish. The three escapees take over the Hilliard home, using it as an unsuspected resting place while a police manhunt scours the city for them. Glenn Griffin finds Dan Hilliard to be no pushover, but rather a determined fighter out to protect his home and family from this criminal invasion. But is a middle-aged businessman a match for three wiley killers?
Glen, Hal and Sam are three escaped convicts who move in on and terrorize a suburban household.
Joseph Hayes
Languages : English, Italian
Subtitles : English, Turkish, Slovenian, Arabic, Romanian, Serbo-Croatian
Keywords: Drama; Thriller